The relationship between inter-parental conflicts and externalizing behaviour problems among adolescents - Esfandyari, Bahador; Baharudin, Rozumah; Nowzari, Leila (Eurojournals, 2009)
This paper reviews several empirical studies which highlight that externalizing behaviour problems among adolescents are strongly influenced by their inter-parental conflict. Inter-parental conflict is indicated as a factor contributing to externalizing behaviour problems. A strong relationship between externalizing behaviour problems and inter-parental conflict has been reported in several past studies. Based on the findings of many studies, there is a significant relationship between positive family relations with the decrease level of externalizing behaviour problems, such as social aggression among children. Similarly, there are a number of important findings which indicated that children living in discordant and violent homes are at high risk of psychopathology. In addition, witnessing inter-parental conflict was related to a host of youth problematic behaviours including aggression, delinquency, and substance abuse. Thus, this paper aims to review the relationship between inter-parental conflicts and externalizing behaviour problems among adolescents.